Livros de devoção a Santa Bárbara: uma ausência nas livrarias dos mosteiros de São Salvador de Vairão e de Refojos de Basto - Mendes, Paula Almeida (2024)
The hagiography of Saint Barbara, of oriental origin, was widely disseminated thanks to the Legenda Aurea by Jacques de Voragine, which stimulated, especially from the end of the 15th century, the production of individual "Lives" and prayers dedicated to the virgin and martyr of Nicomedia. These texts contributed, to a large extent, to the crystallization of the cult and devotion around Saint Bárbara, invoked, above all, to protect the faithful from thunder and sudden death: this is attested by a significant set of works produced in Portugal, from the 16th century. The Earthquake that struck the city of Lisbon, on November 1, 1755, and its consequences contributed to the revaluation of devotion to Saint Bárbara, expressed in hagiographic texts, prayers and images that sought to respond to a set of concerns felt by the Portuguese population. With this issue as a backdrop, this communication aims to draw attention to the texts that, in Portugal, throughout the Modern Period, support the devotion and cult around Saint Barbara, trying to understand the reasons that justify its absence in libraries of the monasteries of Refojos de Basto and São Salvador de Vairão.